Morphisms Between Grassmannian Complex and Higher Order Tangent Complex - Hussain, Sadaqat; Siddiqui, Raziuddin (Communications in Mathematics and Applications, 2019)
In this article we extend the notion of tangent complex to higher order and propose morphisms between Grassmannian subcomplex and the tangent dialogarithmic complex for a general order. Moreover, we connect both these complexes and prove the commutativity of resulting diagram. The interesting point is the reappearance of classical Newton's Identities here in a completely different context to the one he had.